Emergency general surgery: Impact of hospital and surgeon admission case volume on mortality. Issue 6 (June 2021) - Wohlgemut, Jared M.; Ramsay, George; Bekheit, Mohamed; Scott, Neil W.; Watson, Angus J.M.; Jansen, Jan O.
Abstract : Supplemental digital content is available in the text. Abstract : BACKGROUND: Emergency general surgery (EGS) is a high-volume and high-risk surgical service. Interhospital variation in EGS outcomes exists, but there is disagreement in the literature as to whether hospital admission volume affects in-hospital mortality. Scotland collects high-quality data on all admitted patients, whether managed operatively or nonoperatively. Our aim was to determine the relationship between hospital admission volume and in-hospital mortality of EGS patients in Scotland. Second, to investigate whether surgeon admission volume affects mortality. METHODS: This national population-level cohort study included EGS patients aged 16 years and older, who were admitted to a Scottish hospital between 2014 and 2018 (inclusive). A logistic regression model was created, with in-hospital mortality as the dependent variable, and admission volume of hospital per year as a continuous covariate of interest, adjusted for age, sex, comorbidity, deprivation, surgeon admission volume, surgeon operative rate, transfer status, diagnosis, and operation category. RESULTS: There were 376, 076 admissions to 25 hospitals, which met our inclusion criteria. The EGS hospital admission rate per year had no effect on in-hospital mortality (odds ratio [OR], 1.000; 95% confidence interval [CI], 1.000–1.000). Higher average surgeon monthly admission volume increased the odds of in-hospital mortality (>35 admissions: OR, 1.139; 95% CI, 1.038–1.250; 25–35 admissions: OR, 1.091; 95% CI, 1.004–1.185; <25 admissions was the referent). CONCLUSION: In Scotland, in contrast to other settings, EGS hospital admission volume did not influence in-hospital mortality. The finding of an association between individual surgeons' case volume and in-hospital mortality warrants further investigation. LEVEL OF EVIDENCE: Care management, Level IV.